Acinetobacter baumannii: an evolving and cunning opponent - Shi, Jingchao; Cheng, Jianghao; Liu, Shourong; Zhu, Yufeng; Zhu, Mingli (Frontiers in Microbiology, 2024)
Acinetobacter baumannii is one of the most common multidrug-resistant pathogens causing nosocomial infections. The prevalence of multidrug-resistant A. baumannii infections is increasing because of several factors, including unregulated antibiotic use. A. baumannii drug resistance rate is high; in particular, its resistance rates for tigecycline and polymyxin—the drugs of last resort for extensively drug-resistant A. baumannii—has been increasing annually. Patients with a severe infection of extensively antibiotic-resistant A. baumannii demonstrate a high mortality rate along with a poor prognosis, which makes treating them challenging. Through carbapenem enzyme production and other relevant mechanisms, A. baumannii has rapidly acquired a strong resistance to carbapenem antibiotics—once considered a class of strong antibacterials for A. baumannii infection treatment. Therefore, understanding the resistance mechanism of A. baumannii is particularly crucial. This review summarizes mechanisms underlying common antimicrobial resistance in A. baumannii, particularly those underlying tigecycline and polymyxin resistance. This review will serve as a reference for reasonable antibiotic use at clinics, as well as new antibiotic development.